Biological fractionation of stable Ca isotopes in Göttingen minipigs as a physiological model for Ca homeostasis in humans. Issue 6 (1st November 2016) - Heuser, Alexander; Eisenhauer, Anton; Scholz-Ahrens, Katharina E.; Schrezenmeir, Jürgen
ABSTRACT: In order to investigate fractionation of calcium (Ca) isotopes in vertebrates as a diagnostic tool to detect Ca metabolism dysfunction we analyzed the Ca isotopic composition (δ 44/40 Ca = [( 44 Ca/ 40 Ca)sample /( 44 Ca/ 40 Ca)reference ]−1) of diet, faeces, blood, bones and urine from Göttingen minipigs, an animal model for human physiology. Samples of three groups were investigated: 1. control group (Con), 2. group with glucocorticosteroid induced osteoporosis (GIO) and 3. group with Ca and vitamin D deficiency induced osteomalacia (−CaD). In contrast to Con and GIO whose average δ 44/40 Cafaeces values (0.39 ± 0.13‰ and 0.28 ± 0.08‰, respectively) tend to be lower than their diet (0.47 ± 0.02‰), δ 44/40 Cafaeces of −CaD (−0.27 ± 0.21‰) was significantly lower than their δ 44/40 Cadiet (0.37 ± 0.03‰), but also lower than δ 44/40 Cafaeces of Con and GIO. We suggest that the low δ 44/40 Cafaeces of −CaD might be due to the contribution of isotopically light Ca from gastrointestinal fluids during gut passage. Assuming that this endogenous Ca source is a common physiologic feature, a fractionation during Ca absorption is also required for explaining δ 44/40 Cafaeces of Con and GIO. The δ 44/40 Caurine of all groups are high (>2.0‰) reflecting preferential renal reabsorption of light Ca isotopes. In Göttingen minipigs we found a Ca isotope fractionation between blood and bones (Δ 44/40 Cablood-bone ) of 0.68 ± 0.15‰.